2017
DOI: 10.1155/2017/1287698
|View full text |Cite
|
Sign up to set email alerts
|

New Class of Antimicrobial Agents: SBA-15 Silica Containing Anchored Copper Ions

Abstract: The paper is about a new class of antimicrobial functional nanomaterials. Proposed compounds are based on SBA-15 porous silica matrices and contain anchored copper ions. Thanks to the immobilization of functional groups the compounds are safer for environment than commonly used disinfectant agents. We prepared and examined silica based materials containing two concentrations of copper-containing groups: 10 and 5%. For the reference we prepared samples containing free-standing CuO molecules in the structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Such materials can find applications mainly as antimicrobial coatings. As we reported earlier [42], functionalized mesoporous silica can present very unusual biocidal properties. The rate of bacteria elimination strongly depended on the concentration of metal-containing molecules, but this dependency was not linear and not monotonous.…”
Section: Introductionsupporting
confidence: 62%
“…Such materials can find applications mainly as antimicrobial coatings. As we reported earlier [42], functionalized mesoporous silica can present very unusual biocidal properties. The rate of bacteria elimination strongly depended on the concentration of metal-containing molecules, but this dependency was not linear and not monotonous.…”
Section: Introductionsupporting
confidence: 62%
“…Recently, there have been many papers in the literature that have highlighted an innovative approach for functionalizing well-known structures by combining porous materials such as an oxide matrix carrier, e.g., a polymer, silicon oxide, titanium oxide, or zinc oxide, with the ionic form of metals or with metallic nanoparticles [ 44 , 45 , 46 , 47 ]. The chemically modified fumed silica seems to be the most promising inorganic structure due to the immobilization of silver on the surface via unsaturated chemical bonds [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Singh et al, a significantly lower glucose elevation in Cd-exposed animals was detected [ 70 ]. Many studies have shown that the metal concentration in the blood significantly affects the duration of type 1 diabetes and the degree of metabolic control [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: The Risk Of T1dm Development Associated With Exposure To Sel...mentioning
confidence: 99%